Writing an Effective Anticorruption Law - Messick, Richard E.; Kleinfeld, Rachel (World Bank, Washington, DC, 2012)
The note looks at effective anticorruption legal instruments. However, law enforcement measures are not the first or necessarily the preferred method of defense. An informed citizenry, a government imbued with a service ethic, and other measures can be more effective in combating corruption. But tailoring the law to improve enforcement capacity generally encompasses a variety of statutes that prohibit bribery, nepotism, conflicts of interest, and favoritism in the award of contract or the provision of government benefits. And writing such laws containing "bright-line rules" in contrast to those containing standards open to interpretation by enforcement agencies may make it easier to monitor compliance and enforcement, but also rob the law of flexibility. Such laws often must be simplified to the point of arbitrariness-making them harder to accept than broadly-worded standards, which often conform to intuitive social understandings. The cost of bright-line rules are often more than offset by their deterrence value and their value in facilitating monitoring in countries with weak enforcement agencies. However, no statute can avoid some open-textured provisions. When a section in an anticorruption law must leave something open to question, one way to reduce enforcers' discretion is to establish a procedure for obtaining advance rulings. Finally, the author recommends laws that help bring corruption to light, such as a freedom of information law.